KONTRIBUSI CARA BELAJAR DAN STATUS SOSIAL EKONOMI KELUARGA TERHADAP PRESTASI BELAJAR SISWA BERPRESTASI KELAS XI JURUSAN TEKNIK AUDIO VIDEO (TAV) SMK NEGERI DAN SWASTA DI KOTA PADANG - Dina Amelia Amelia; Putra Jaya; Legiman Slamet (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
The purpose of this study was to reveal the contribution of student learning and  Family Socioeconomic Statuson student achievement outstanding Class XI Department of Audio Video (TAV) Public and Private SMK Padang. This research is a correlationaldescriptive study. The study population totaled 69 students and the sample amounted to 41 outstanding students of class XI and SMK Padang Private in the Academic Year 2012/2013. Sampling technique proportional random sampling. Student learning outcomes data is obtained from the public and private vocational school student in the city of Padang. While data on student learning and Family Socioeconomic Status were collected through a questionnaire using a Likert scale that has been tested for validity and reliability. Data were analyzed using a computer program SPSS version 16.0. The results of data analysis showed: (1) How to study and Family Socioeconomic Status together accounted for 56.6% of the outstanding student achievement in public and private SMK Padang; (2) How to Learn accounted for 30.1% of the outstanding student achievement in public and private SMK Padang; (3) Family Socioeconomic Status accounted for 15.13% of the outstanding student achievement in public and private SMK Padang.Keywords: How to Learn, Family Socioeconomic Status, Learning achievement, correlational descriptive, proportional random sampling.